Comparisons of Electron Transfer Reactions in a Cyanobacterial Tetrameric and Trimeric Photosystem I Complexes. (2nd March 2018) - Shelaev, Ivan V.; Mamedov, Mahir D.; Gostev, Fedor E.; Aybush, Arseny V.; Li, Meng; Nguyen, Jonathan; Bruce, Barry D.; Nadtochenko, Victor A.
Abstract: Photosystem I (PSI) is a Type‐I reaction center and is the largest photosynthetic complex to be characterized. In cyanobacteria, PSI is organized as a trimer with a three‐fold axis of symmetry. Recently, a tetrameric form of PSI has been identified in cyanobacteria. Plastids in plants and algae only contain monomeric PSI, suggesting that tetrameric PSI may be key in the transition from ancestral cyanobacterial trimeric PSI to plant/algal monomeric PSI. We have investigated the kinetics of electron transfer to the initial acceptor in PSI tetramer isolated from Chroococcidiopsis  TS‐821. Using a pump–probe technique with 25 fs low‐energy, 720 nm pump pulses, we measure the ultrafast (<100 fs) conversion of a delocalized exciton into a charge‐separated state between the primary donor P700 and the primary acceptor A0 . Comparison with previous pump–probe analysis of the trimeric PSI complexes from Synechocystis sp PCC 6803 (Shelaev et al . [2010] Biochim Biophys Acta, 1797, 1410–1420) reveals that the tetrameric (PSI) complexes from Chroococcidiopsis  sp TS‐821 are quite similar. The transfer of an electron from the A0 to the following acceptor A1 (phylloquinone) takes place in a time frame of about 30 ps, which is slightly longer compared to PSI trimeric complex (~24 ps). The slight spectral differences between trimeric and tetrameric PSI complexes are discussed. Abstract : Electron Transfer Kinetics in a Tetrameric Photosystem I Complex—Tetrameric PSI (Cryo‐EM structure shown) isolated from the thermophilic cyanobacterium, Chroococcidiopsis sp. TS‐821 has been investigated using a pump–probe technique with 25 fs low‐energy pump pulses centered at 720 nm. We observe ultrafast (<100 fs) conversion of delocalized exciton into a charge‐separated state of oxidized primary donor P700 and reduced primary acceptor A0. Comparison of electron transfer between trimeric and tetrameric PSI complexes suggests that the tetrameric PSI has similar kinetics to the trimeric PSI complexes from Synechocystis sp PCC 6803, yet the tetramer has slight spectral differences.